The assessment of surface roughness and microleakage of eroded tooth-colored dental restorative materials - AL NAQSHABANDI, THULFIQAR ALI (Wolters Kluwer - Medknow, 2014)
Objectives: To investigate the effect of acidic solution on surface roughness and microleakage of tooth-colored restorative materials. Materials and Methods: A 160 box-shaped cavities were prepared on the buccal surfaces of 160 human molars, and assigned to four groups: Group A restored with Ketac™ Molar Easymix, Group B with Fuji II™ LC, Group C with Ketac™N100, and Group D with Filtek™ Z250, and subdivided into study and control groups (n = 20). Study groups were immersed in lemon juice (pH = 2.79) for 24 h, whilst controlgroups in deionized distilled water. All samples were immersed in 2% methylene blue dye, sectioned into two equal halves for surface roughness, and microleakage tests. Data were analyzed using Mann–Whitney and Kruskal–Wallis tests at P < 0.05. Results: There was a significant difference in surface roughness of Ketac™ Molar, Fuji II™LC, and Ketac™N100. No significant difference was found in microleakage of Ketac™ Molar and Fuji II™LC; however, there were significant differences in the gingival margin of Ketac™N100, and the occlusal margin of Filtek™Z250. Conclusions: All glass ionomer cements were eroded after exposure to the acidic drink. Filtek™ Z250 and Ketac™ Molar Easymix showed more microleakage. All materials showed more microleakage at the gingival margins.